Gender-Marked Metaphors: Influence of Grammatical Gender and Frequency on Referential Choice of Metaphorical Name of the Person in the Russian Language; Procedia - Social and Behavioral Sciences; Vol. 200 : Language and culture - Rezanova Z. I. Zoya Ivanovna (2015, 2015)
Title screen